Corporate Governance, Board Characteristics and Performance of Indian Banks: An Empirical Study - Bezawada, Brahmaiah; Adaelli, Sager Reddy (International Journal of Economics and Financial Issues, 2020)
The paper examines the corporate governance, board characteristics, performance and asset quality of Indian banks and investigates the impact of a set of board characteristics on performance and asset quality of banks. We use a sample of 34 scheduled commercial banks, for ten years from 2009 to 2018, accounting for about 90 per cent of the total banking assets and banking business India. We measure bank performance by return on assets (ROA) and asset quality of banks by ratio of net non-performing assets (NNPA) and document evidence on the role of the board characteristics on performance and asset quality of banks. The study finds that the board size and percentage of independent directors have significantly positive impact on ROA. The percentage of executive directors is having significantly negative relationship with the ROA. The board size and percentage of independent directors have significantly negative relationship with banks’ NNPAs. The research suggests that the board of directors play a significant role in bank governance in India. The paper contributes to the literature on the corporate governance of banks in India, which is one of the emerging economies of the world. The research results provide some insights of corporate governance to the RBI for considering appropriate policy guidelines on corporate governance to banking industry in India. Keywords: Corporate governance, Board characteristics; Performance of banks, Non-performing assets JEL Classifications: G21, G28, G32 DOI: https://doi.org/10.32479/ijefi.9536